Service Strategy and Policy for the Disabled - Djunaidi, Djunaidi (Graduate Program Magister Manajemen Pendidikan, 2022)
This study aims to describe the strategy and service policies for the disabled. People with disabilities really need attention from family, community and government. In matters of service, this group should be given special and adequate services in accordance with the law that has been enacted. This research method uses descriptive qualitative method. The sources used to obtain data in this research are journals and books that support the research study. The researcher also looks at the phenomena that occur regarding service strategies and policies for the disabled so that they can be related to this research. This study presents several findings, namely issues related to people with disabilities and cases of people with disabilities that have attracted worldwide attention, services provided for people with disabilities and laws and regulations made specifically for people with disabilities and the implementation of these laws for people with disabilities.